The Method Afro-Brazilian cardio - Peter Pan Industries (Roseland, N.J. Peter Pan Industries, 1993)
Let your body experience the energy of Afro-Brazilian moves to the uplifting beat of a live percussion band. Each of the three workouts takes you a step further toward a complete body toning experience. The rhythmic, low impact dance moves from Africa and Brazil work your entire body while energizing your mind.
Led by Beth Lane.
DVD (Regional coded, NTSC) ; Standard full frame (1.33:1) ; Single layer ; Dolby Digital.
In English.
Keywords: Exercise for women; Physical fitness for women; Aerobic dancing